Analysis of Factors Affecting the Supply of Onion in Brebes Regency - G, Vonny Faradila; Antriyandarti, Ernoiz; Khomah, Isti (Politeknik Pertanian Negeri Payakumbuh, 2022)
This analysis of the supply of onion in Brebes Regency is done using the methods of descriptive and analytic, and secondary data time series for 21 years (1998-2018). This study also utilizes the analysis of multiple linear by entering the model analysis of the distributed lag model with adjustment Nerlove (Partial Adjustment Model). The supply function is estimated with the approach of total production. The results of the multiple linear regression analysis obtained the factors that affect positively to the offer of onion in Brebes Regency is a vast harvest of onion in year t, the number of onion production in year t-1, the price of onions in year t-1, the price of garlic in year t-1, the average rainfall in year t, and interest rate in year t. The factor that negatively affects the offer is the price of urea fertilizer in year t. The most influential factor to the offer of onion in Brebes Regency is a vast harvest of onion in year t with the standardized regression coefficient of 0,889. The elasticity of supply for the area variable harvesting onions in year t is positive and is elastic with E greater than 1, namely 1,328 for the short-term and 1,832 for the long term. Elasticity is inelastic with E value less than 1 is a variable amount of production in the previous year i.e. 0,275 short-term and 0,379 long-term prices of garlic in the previous year with a value of 0,105 short-term and of 0.145 long-term, the price of onions in the previous year with a value of -0,143 short-term and -0,197 the long term, the interest rate in year t, namely 0,136 and 0,188, and the average rainfall in year t with the value of -0,218 short-term and -0,301 the long term.